Detecting and tracking drift in quantum information processors - Timothy Proctor (Nature Portfolio, 2020)
Time-dependent errors are one of the main obstacles to fully-fledged quantum information processing. Here, the authors develop a general methodology to monitor time-dependent errors, which could be used to make other characterisation protocols time-resolved, and demonstrate it on a trapped-ion qubit.